TINJAUAN TERHADAP PLTS 24 KW ATAP GEDUNG PT INDONESIA POWER PESANGGARAN BALI - Ketut Vidhia Kumara; I Nyoman Satya Kumara; Wayan Gede Ariastina (Jurnal SPEKTRUM, 2018)
PT. Indonesia Power unit Pesanggaran is one of the power generation companies in Bali, which has also participated in the development of renewable energy by installing solar PV with a capacity of 24 KW. In this research, reviews was conducted to know the condition of the solar PV plant. Review is carried out by conducting observation in the field, reviewing technical data of solar PV components, and also interviews with the staff who operate and maintain the solar PV. Through reviews it was found that the design and installation of solar PV plant is good and follows good practice of solar PV installation for optimum energy production. Due to plant location at GPS coordinate of -8,72, 115,21 therefore the solar module has been installed facing north or azimuth 0o. This module is placed on the roof of Building A, thereby reducing the cost to construct mechanical supports. The solar module was installed with a slope angle of 22o approaching the optimum slope angle. The components of the PV plant are good as they bear international standards. The solar module is CHN240-60P polycrystalline silicon with 60 cells that caccries CE certificate (Conformité Europeenne). Also, the inverter is three units of ABB PVS300-TL-800W-2 with AC output of 8,000 W which are also carries CE certificate and others. The quality of technical specifications of solar PV components and also installation of the plant has direct influence on the energy production of the plant and these have been properly implemented on the 24 KW Indonesia Power solar PV plant.